Estudo de otimização do processo de obtenção de biodiesel de segunda geração - Ponte, Flávio Albuquerque Ferreira da (2012)
Biodiesel is a renewable fuel and can be used to replace partially or totally, the diesel fuel in compression ignition engines. This biofuel can be obtained from the transesterification of vegetable oils with alcohols. Some of the major challenges in biodiesel production are: cost and availability of raw material. Castor oil is one of the most important possible feedstocks among several options currently available in Brazil for biodiesel production. The castor oil is harmful to human health and therefore cannot be consumed as a food. Pure castor oil biodiesel does not fulfill parameter as gravity or viscosity in the Brazilian biodiesel specifications of ANP (National Agency of Petroleum, Natural Gas and Biofuels). Other oleaginous seeds are also used for biodiesel production like soybean, canola, and cotton. This study aimed to use blends of castor oil with cotton, canola and soybean oils in order to optimize the production of second generation biodiesel. The use of these blends could reduce the cost of production, and produce second generation biodiesel that fulfill the brasilian’s specifications. Biodiesel was produced from binary mixtures of vegetable oils in different mass ratios by reaction of alkaline transesterification by homogeneous catalyst using methanol and ethanol as alcohol. The mass ratio methanol/catalyst/oil (% w/w) were 20/0,6/100 and ethanol/catalyst/oil (% w/w) were 43/0,6/100. The analysis of the conversion reaction was carried out using the technique of Nuclear Magnetic Resonance of Hydrogen protons (1H-NMR). The physicochemical characterizations were performed according to ABNT, NBR, ASTM and CEN standards. As the analysis of characterization, all specifications biodiesels of pure oils and blends comply with the requirements of the limits allowed by ANP. The best result was obtained for blends of castor and cotton oils (20:80) to the methanolysis reaction parameters: temperature 60 °C and reaction time of 40 minutes and the same proportion to the ethanolysis: 60 °C for 5 minutes. As for castor: soybean and castor; canola was the best optimization in the ratio (30:70) for the route in the methyl reaction parameters: temperature of 25 ° C and reaction time of 40 minutes and the best ethylic route result was in the ratio (20:80) with the parameters: temperature 60 °C for 5 minutes. The results indicated that binary blends of vegetable oils may be an alternative to use less edible raw material for biodiesel production.